2022
DOI: 10.1021/acs.jafc.2c04789
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MPFAST Promotes Proliferation and Fatty Acid Synthesis of Bovine Mammary Epithelial Cell by Sponging miR-103 Regulating PI3K-AKT Pathway

Abstract: Long noncoding RNAs (lncRNAs) have an essential role in mammary gland development and lactation. Our earlier study showed that the lncRNA mammary proliferation and fatty acid synthesis-associated transcript (MPFAST) is highly expressed in the Holstein cow mammary gland during the middle lactation period compared to the dry period, which indicates its potential role in lactation. Therefore, gain- and loss-of-function experiments were performed on bovine mammary epithelial cells (BMECs) by cell counting kit 8 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…It has been well-documented that the PI3K/Akt pathway plays a vital part in cell survival, proliferation, and metabolism [40,41]. In the present study, we found that DOPC inhibited the activation of the PI3K/Akt pathway, while the activator of Akt reversed the inhibitory effects of DOPC on HC11 proliferation.…”
Section: Discussionsupporting
confidence: 62%
“…It has been well-documented that the PI3K/Akt pathway plays a vital part in cell survival, proliferation, and metabolism [40,41]. In the present study, we found that DOPC inhibited the activation of the PI3K/Akt pathway, while the activator of Akt reversed the inhibitory effects of DOPC on HC11 proliferation.…”
Section: Discussionsupporting
confidence: 62%
“…The PI3K–Akt signaling pathway is a canonical pathway involved in mammary development and lipid metabolism [ 75 ]. Liu et al [ 76 ] found that the lncRNA mammary proliferation and fatty acid synthesis-associated transcript promotes proliferation and fatty acid synthesis in bovine mammary epithelial cells by sponging miR-103, which regulates the PI3K–Akt pathway. Among the downregulated gene enrichment pathways, MAPK signaling pathways are related to higher milk yields in cattle [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can bind to the 3′ untranslated region or coding region of the target gene sequence through complementary base pairing and bind to the 5′ untranslated region of the target mRNA to regulate gene expression and further affect the protein expression level inside cells (Jabed et al, 2012). miRNA expression is characterized by developmental stage specificity and tissue specificity and plays a specific role in regulating biological functions such as mammary gland development (Liu et al, 2022), lactation process (Dysin et al, 2021), fat metabolism (Chen, Chu, Wang, Fan, et al, 2019;Chen, Chu, Wang, Sun, et al, 2019), and innate immunity (Yuan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of candidate gene screening and sequencing and comparative genomics research methods, more genes and regulatory factors related to fat milk metabolism have been discovered. Their functions are verified, and miRNA is one of the critical regulatory factors (Liu et al., 2022). Milk is a highly complex liquid made up of water (86–88%), fat (3–5%), protein (3.3–3.6%), carbohydrates (4.5–5.0%), minerals (0.7%) and enzymes, as well as many other minor components (Foroutan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation